Is socially responsible investing just screening? Evidence from mutual funds - Markus Hirschberger; Ralph E. Steuer; Sebastian Utz; Maximilian Wimmer (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This paper presents the results of an empirical study concerning conventional and socially responsible mutual funds.We apply a sophisticated operations research algorithm embedded in inverse portfolio optimization on financial market data, ESG-scores and CRSP fund data. Due to our results we cannot find strong evidence of di erences between conventional and socially responsible mutual funds. In particular, the calculated risk tolerance parameters describing the real portfolio composition best show that socially responsible mutual funds may be even less concerned about the ESG-scores in the preference functional than conventional funds.
Keywords: C61; G11; 330; socially responsible investing; inverse portfolio selection; Ethische Geldanlage; Investmentfonds; Portfolio-Management; Vergleich; Schätzung; Welt